PLAY ACTIVITIES IN A PRESCHOOL EDUCATIONAL ORGANIZATION (International journal of artificial intelligence, 2025)
play activities in preschool educational organizations hold a central place in the comprehensive development of children. This activity is an important tool for forming children's cognitive, socio-emotional, physical, and speech skills. This article analyzes the pedagogical significance of play activities in preschool educational organizations, their impact on children's development, as well as methods for creating an effective play environment. It examines types of play, the educator's role in the play process, and play-based learning strategies.